Deciphering the Role of the Coagulation Cascade and Autophagy in Cancer-Related Thrombosis and Metastasis - Hill, Charlotte Nicole; Hernández-Cáceres, Maria Paz; Asencio, Catalina; Torres, Begoña; Solis, Benjamin; Owen, Gareth I. (Frontiers in Oncology, 2020)
Thrombotic complications are the second leading cause of death among oncology patients worldwide. Enhanced thrombogenesis has multiple origins and may result from a deregulation of megakaryocyte platelet production in the bone marrow, the synthesis of coagulation factors in the liver, and coagulation factor signaling within the tumor microenvironment (TME). While a hypercoagulable state has been attributed to factors such as thrombocytosis, enhanced platelet aggregation and Tissue Factor (TF) expression on cancer cells, further reports have suggested that coagulation factors can enhance metastasis through increased endothelial-cancer cell adhesion and enhanced endothelial cell activation. Autophagy is highly associated with cancer survival, acting as a double-edged sword that can both inhibit and promote cancer progression. We discuss herein that the coagulation system is not merely a bystander in cancer metastasis, but instead an integral part of the multifaceted approach taken by the malignant cell to survive, propagate and ultimately exhaust the body's capacity to function. We speculate that the malignant cell may use common mechanisms to hijack immune cells, endothelial cell (ECs), hematopoietic cells and platelets to integrate with the coagulation system for its own end. In this review, we postulate that a common mechanism present in each of these components may be the hijacking of the autophagy pathway. Relevant to the coagulation cascade, we also examine the role of autophagy-related pathways in cancer treatment. In this review, we aim to bring to light possible new areas of cancer investigation and elucidate new strategies for future therapeutic intervention.